Intralingual Translation and Its Place within Translation Studies – A Theoretical Discussion - Korning Zethsen, Karen; Hill-Madsen, Aage (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2016)
Roman Jakobson’s tripartite typology of translation is accepted by many translation scholars as a broad definition of translation and is frequently included in the beginning of textbooks introducing Translation Studies. However, when it comes to the research carried out within Translation Studies, focus is overwhelmingly set on interlingual translation, or translation proper. A few scholars explicitly argue against the inclusion of intralingual and intersemiotic translation in a definition of translation whereas some provide arguments or discussions of concepts central to Translation Studies which explain the marginal status of intralingual and intersemiotic translation. The aim of this article is to review these arguments and to discuss the place of intralingual translation within Translation Studies. On this basis, the article suggests a criterial definition of translation to be used for scientific purposes within the field of Translation Studies, a definition which fully includes intralingual translation.